A new genus of Phaneropterinae (Orthoptera: Ensifera: Tettigoniidae) from Central Africa - Massa, Bruno (Zootaxa, 2014)
The new genus Pseudoplangia is described for Plangia laminifera Karsch, 1896. Its general aspect is similar to that of the genus Plangia Stål, 1873, but it differs remarkably in the vertex width, in the shape of eyes, that are oval and elongate, in the length of mid femora, that are shorter than pronotum length, in the shape of fore and mid legs that are very much laterally compressed, and in the presence of broad-based spines on the hind tibiae.